Evaluating the performance of roadside barrier using surrogate devices - Soltani, M.; Ramli Sulong, N.H.; Karim, M.R. (2011)
Evaluating the crash test is one of the most important stages of providing safety on roads. Nowadays, two kinds of equipments named surrogate devices are used to evaluate guardrails specifically, pendulum and bogie vehicle. This paper provides a review of usage these equipments and procedure to test guardrails. Advantages of each method are analyzed and also for each method, suitable application is recommended. The result of tests shows that, the bogie and pendulum tests are suitable surrogate devices to evaluate the performance of the guardrail.